Investigating the effects of the teaching and learning process in using the blended learning approach on the blended courses performance: a case study of Universiti Teknologi MARA Cawangan Melaka / Mazlan Salleh, Rani Diana Othman and Wan Hartini Wan Hassan (UiTM Press, 2018)
The aims of this study was to investigate whether there are positive effects in the teaching and learning process with the blended learning approach by looking at the performances of the blended courses from the lecturers' perspectives. The study was conducted on 81 lecturers teaching diploma and bachelor degree levels in Universiti Teknologi MARA Cawangan Melaka. Lecturers were asked for their perceived responses on the students' level of activeness, either active, less active or inactive, in the blended approach when conducting classes. An independent sample t-test was administered to determine significant differences in the perceived responses on the students' level of activeness in the process of teaching and learning with the blended approach. Lecturers'characteristics; gender group, age group, level of study taught, years of experience using blended learning approach and status of blended course conducted were emphasized.